Peningkatan Sradha Bhakti Dan Karakter Siswa Sekolah Dasar Di Desa Mayong Melalui Tri Hita Karana - Ketut Sri Wahyuni; Ni kadek Yuni Ariningsih; I Putu Ariyasa Darmawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Tri Hita Karana as an effort to realize harmony and as an effort to succeed the four goals of human life called Catur Purusha Artha, a balanced attitude to life between devotion to God, serving fellow humans and protecting the natural environment, the teachings of Tri Hita Karana will be balanced if its implementation carried out properly, a life activity that will continuously be pursued so that the harmonious relationship is truly integrated on an ongoing basis. Ida Sang Hyang Widhi Wasa. Tri Hita Karana comes from the word Tri which means three, hita which means happy and the means of which cause. So Tri Hita Karana means the three causes of Hindu's happiness. The teachings of Tri Hita Karana are divided into three parts of the prahyangan, Pawongan, palemahan. Prahyangan is how we get closer to God, then Pawongan is human relationship with other humans, and the palemahan is how we maintain the environment.The value of the student character can be improved through the practice of Tri Hita Karana so every student will have a skil or ability to understand religion and apply the teachings of Tri Hita Karana